Stabilization of Sedimentary Soil with Cement-EPS on Direct Shear Strength Value - Suyadi Suyadi; Nurul Marfuah; Achmad Bakri Muhiddin; Kartika Sari; Shafwan Monanda (International Association of Lowland Technology, 2022)
Sediment is material resulting from the erosion process that settles in waterways, rivers and reservoirs. Excessive sedimentation at the bottom of the reservoir will reduce the effective volume of the reservoir which will affect the design life of the reservoir or the service life of the reservoir (siltation). The sedimentation events that occurred in the Bili-bili Reservoir are increasingly worrying because they can criticize the continued functioning of the reservoir. This is a problem that really needs to be taken seriously so that it doesn't have an impact in the future. So, a study is needed on reservoir sedimentary soils Bili-bili to determine the physical and mechanical properties of the soil, This study aims to determine the characteristics of the sedimentary soil used, the effect of adding a variety of cement and EPS - cement and curing to the shear strength value of the soil on the test Direct Shear. The tests carried out were tests of physical properties and mechanical properties of the Bili-bili Reservoir sediment soil with mixed variations, namely the addition of 3%, 5%, 7% and 9% cement, to 0.5% and 0.75% EPS with a curing period of 7 days, 14 days and 28 days and from the results of the study, it was found that the addition of cement to sedimentary soils can increase the specific gravity value and decrease the plasticity index of the soil, where cement can be used as a material for silt soil stability and the silt soil shear strength increases in line with the addition of cement content and increasing curing days.